Diuretic activity of 2-((4-amino-5-R-4H-1,2,4-triazole-3-yl)thio)acetohydrazides - D. M. Danilchenko; А. А. Safonov (Zaporožskij Medicinskij Žurnal)
Introduction. Diuretic drugs occupy large niche in the pharmaceutical market due to the wide range of applications (reduction of edema in heart and vascular disease, kidney disease, decreasing the pressure, removing poisoning toxins).